2018
DOI: 10.1038/s41426-018-0118-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomics of Campylobacter concisus : Analysis of clinical strains reveals genome diversity and pathogenic potential

Abstract: In recent years, an increasing number of Campylobacter species have been associated with human gastrointestinal (GI) diseases including gastroenteritis, inflammatory bowel disease, and colorectal cancer. Campylobacter concisus, an oral commensal historically linked to gingivitis and periodontitis, has been increasingly detected in the lower GI tract. In the present study, we generated robust genome sequence data from C. concisus strains and undertook a comprehensive pangenome assessment to identify C. concisus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 60 publications
1
19
0
Order By: Relevance
“…They have also been used to detect similarity and differences in genes of particular strains isolated from the same host. For example, Gemmell et al [20] used phylogenetic analysis to investigate the virulence properties and adaptive skills of Campylobacter concisus (C. concisus) isolated from the gastrointestinal tracts of humans and reported that there was no difference between oral and gut C. concisus .…”
Section: Introductionmentioning
confidence: 99%
“…They have also been used to detect similarity and differences in genes of particular strains isolated from the same host. For example, Gemmell et al [20] used phylogenetic analysis to investigate the virulence properties and adaptive skills of Campylobacter concisus (C. concisus) isolated from the gastrointestinal tracts of humans and reported that there was no difference between oral and gut C. concisus .…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the microbial community observed in atherothrombotic samples is similar to that observed in subgingival samples [35]. However, no periodontal species have been identified by WGS in vascular samples [36] but they have been identified by WGS in other samples [37]. Some studies also identified gut microbiome members within atherothrombotic samples using WGS, however, the results are mixed [38].…”
Section: Microbial Whole Genome Sequencingmentioning
confidence: 69%
“…Therefore, the pathogenic potential may differ depending on the anatomical site in the same host 56 . Depending on the ecological niche, bacteria adapt, leading to varying phenotypic expression and, consequently, different host responses 57 .…”
Section: Discussionmentioning
confidence: 99%